Managing Russian agri-food supply chain networks with power - Vera Belaya; Jon Henrich Hanf (Journal on Chain and Network Science, 2012)
The importance of power is underlined by many scientists who view it as a key behavioural construct. Power distinguishes itself as an effective tool in coordinating and promoting harmonious relationships, solving conflicts, and enhancing performance. An important challenge is to find out what role power plays in managing supply chain networks, paying specific attention to its effects on coordination and cooperation. The aim of our work is to investigate the role of power in supply chain networks in order to work out a strategy that enables supply chain managers to select an effective mix of power mechanisms. We critically examine the existing literature and elaborate on the role of power in supply chain relationships. We work out and test a theoretical model of the effects of power on cooperation and coordination and discuss possible managerial implications of using power as an effective tool for promoting supply chain management. To verify our research hypotheses we conducted semi-structured in-depth expert interviews via telephone about relationships of international food processing companies with their suppliers in Russia and tested the model using the Partial Least Squares (PLS) approach. Depending on the origin of power, it may have different effects on cooperation and coordination. Based on the results of the survey we worked out a special ranking system for the use of power depending on its expected effect on coordination and cooperation. Expert power has the highest ranking among the other types of power for improving coordination. Therefore, we recommend using this strategy as a first priority for improving coordination. The data in our PLS analysis represent only a single perspective in the dyad: food processing companies. Gathering data from other companies' perspectives, such as retailers or agricultural producers, could have produced different (presumably more realistic or complete) findings. Our study offers recommendations for managers about the use of different types of power in managing the Russian agri-food supply chains, with specific attention paid to coordination and cooperation issues. In order to manage supply chain networks successfully, knowledge of different types of power is essential. The developed ranking of different types of power according to their effects on coordination and cooperation is designed to help managers make the right decisions in choosing the appropriate type of power for coordination purposes.
Keywords: 330; power; supply chain networks; supply chain management; Russia; agri-food business